2023
DOI: 10.3390/antibiotics12081257
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing to Predict Mycobacterium tuberculosis Drug Resistance: A Retrospective Observational Study in Eastern China

Mingwu Zhang,
Yewei Lu,
Yelei Zhu
et al.

Abstract: Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (MTB). Whole-genome sequencing (WGS) holds great promise as an advanced technology for accurately predicting anti-TB drug resistance. The development of a reliable method for detecting drug resistance is crucial in order to standardize anti-TB treatments, enhance patient prognosis, and effectively reduce the risk of transmission. In this study, our primary objective was to explore and determine the potential of WGS for as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Another study in Europe revealed that the predictive rates of WGS for LFX and MFX was 83.3 % [ 34 ]. The disparity may be attributed to the genetic diversity of investigated strains, or highly dependent on mutation sites in drug-resistance prediction analysis [ 35 ]. We found the concordance between WGS and phenotypic DST was high for both LFX and MFX, which was consistent with a study in Shanghai with the concordance of 95.3 % for MFX and 93 % for LFX [ 36 ], indicating that WGS provided a promising option for accurate identification of FQs resistant MTB.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Europe revealed that the predictive rates of WGS for LFX and MFX was 83.3 % [ 34 ]. The disparity may be attributed to the genetic diversity of investigated strains, or highly dependent on mutation sites in drug-resistance prediction analysis [ 35 ]. We found the concordance between WGS and phenotypic DST was high for both LFX and MFX, which was consistent with a study in Shanghai with the concordance of 95.3 % for MFX and 93 % for LFX [ 36 ], indicating that WGS provided a promising option for accurate identification of FQs resistant MTB.…”
Section: Discussionmentioning
confidence: 99%